Training Translation Skill Improvement for Indonesian People - Wicaksono, Garda Arif; Parela, Epi; Pradana, M. Rafieq Adi; Andayani, Sri (CV. Tripe Konsultan, 2023)
Community service focus on training translation skill for our people or the translator in Indonesia which become from difference background (province and culture). The purposes of conducting of community service by online to Improvement knowledge, each share one to other participants and also the keynote speaker. Community service method used Training because the servant used some of sequence event likes: gives materials, Question and answer session, Quiz and Evaluation. by conducting Training Translation skill by online many participants are more understanding about how to good translation, more confidence while doing translation and participants suggested that there should be online and scheduled translation classes facilitated by the ngampooz platform